Analyse spatiale des différentes formes de pressions anthropiques dans la réserve de faune de l’Oti-Mandouri (Togo) - Kangbéni Dimobe; Kpérkouma Wala; Komlan Batawila; Marra Dourma; Yao A Woegan; Koffi Akpagana (VertigO)
This study was carried out in 126 plots. 116 woody species (dbh ≥ 10 cm) were identified, including 84 genera and 33 families. The Rubiaceae, Combretaceae and Mimosaceae are the most represented families. This protected area is subject to strong human pressures, including agricultural and pastoral activities, the illegal harvesting of timber, brush fires. The new management rules should aim to preserve to the maximum the Oti-Mandouri natural reserve. Its proximity to the WAP complex leaves open the possibility of a) a subsequent natural repopulation and b) maintaining a corridor to the Oti- Keran national Park.